Whole-cell but not acellular pertussis vaccines induce convulsive activity in mice: evidence of a role for toxin-induced interleukin-1 beta in a new murine model for analysis of neuronal side effects of vaccination - LYNCH, MARINA ANNETTA; MILLS, KINGSTON (American Society for Microbiology, 2001)
Immunization with the whole-cell pertussis vaccine (Pw), while effective at preventing whooping cough in infants, has been associated with local, systemic, and neuronal reactions, including fevers and convulsions in children. In contrast, the new acellular pertussis vaccines (Pa) have a considerably improved safety profile. The lack of an appropriate animal model has restricted investigations into the mechanisms by which neurological reactions are induced by vaccination. Here we describe a novel murine model wherein seizure-like behavioral changes are induced following parenteral administration of Pw. The proinflammatory cytokine interleukin- (IL-1), production of which has been associated with many neurodegenerative conditions, was significantly increased in the hippocampus and hypothalamus of vaccinated animals. Accompanying this change was a decrease in release of the inhibitory neurotransmitters -aminobutyric acid and adenosine in the hippocampus. Seizure-like behavioral changes were significantly reduced following inhibition of IL-1 production by the administration of an inhibitor of IL-1-converting enzyme and were almost completely abrogated in IL-1 receptor type I knockout mice. These results suggest a causal relationship between IL-1 induction and convulsive behavior following Pw vaccination. Significantly, Pa neither increased IL-1 nor induced behavioral changes in mice, but did induce the anti-inflammatory cytokine IL-10. In contrast, administration of active pertussis toxin and lipopolysaccharide, residual in Pw but absent from Pa, also induced convulsive activity. Our findings provide the first direct evidence of an immunological basis for pertussis vaccine reactogenicity and suggest that active bacterial toxins are responsible for the neurologic disturbances observed in children immunized with Pw.
PUBLISHED
Keywords: Physiology